2012
DOI: 10.1111/cyt.12024
|View full text |Cite
|
Sign up to set email alerts
|

Multinational study of oestrogen and progesterone receptor immunocytochemistry on breast carcinoma fine needle aspirates

Abstract: Our experience points to the need for guidelines for hormonal receptor determination and external quality control on cytological material, in order for cytological methods to be used in routine clinical practice with a suitable degree of confidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…In fact, a recent multinational study demonstrated a great variability in the detection of ER and PR in breast FNA specimens because of the different types of cytological preparations and the diverse methods of fixation and immunostaining protocols used by the laboratory participants. The study concluded that the best results were obtained when antigen retrieval and cytospin or thin-layer preparations were used [33]. …”
Section: Ancillary Techniquesmentioning
confidence: 99%
“…In fact, a recent multinational study demonstrated a great variability in the detection of ER and PR in breast FNA specimens because of the different types of cytological preparations and the diverse methods of fixation and immunostaining protocols used by the laboratory participants. The study concluded that the best results were obtained when antigen retrieval and cytospin or thin-layer preparations were used [33]. …”
Section: Ancillary Techniquesmentioning
confidence: 99%
“…Liquid-based cytology (LBC) preparations usually show good reproducibility for ICC and are also suitable for preserving cell samples to provide high-quality DNA and RNA to use in several molecular assays such as PCR, RFLP, and even sequencing [1]. This characteristic makes LBC the ideal system for the evaluation of standard prognostic/predictive markers in breast cancer [2]. However, despite the specific benefits of one or another specimen/fixation technique for a particular assay, in our experience, formalin-fixed paraffin-embedded (FFPE) cell blocks are the best solution for performing ancillary tests on breast FNAB material.…”
Section: Introductionmentioning
confidence: 99%
“…Independently of the preparation technique, cell blocks stain in a highly reproducible manner and can be used to prepare enough slides for large ICC panels as well as for DNA and RNA extraction using standardized protocols thoroughly tested for paraffin-embedded tissues. ICC on FFPE cell blocks can also be performed with the major automatic and commercially available immunohistochemistry platforms, which allows for standardization of techniques using thoroughly validated protocols which lead to highly reproducible assays [2]. Therefore, while ICC and molecular techniques can be performed on several cytologic preparations, we recommend that, if possible, FFPE cell blocks should be obtained for all cases where there might be the need for ancillary studies including ICC or molecular assays.…”
Section: Introductionmentioning
confidence: 99%
“…FNAC is a fast, low-cost technique, with great diagnostic accuracy and with minimum risks to patients [12,13,14,15]. Well-fixed smears along with the cell blocks obtained are optimal adjuncts to perform ancillary techniques, such as immunocytochemistry and molecular tests [16,17,18,19]. Moreover, FNAC has a great intrinsic potential (concerning cytomorphology) to supply additional information to the diagnosis of breast carcinoma for each case [17,18,19], which has been used in attempt to predict molecular phenotypes of breast carcinomas [20].…”
Section: Introductionmentioning
confidence: 99%